BOrderliNe symptoms and suIcide-related outcomes: proTOcol for a systematic review/meta-analysis and an individual patient data meta-analysis (BONITO study). Issue 5 (26th May 2022) - Calati, Raffaella; Romano, Daniele; Lopez-Castroman, Jorge; Turolla, Federica; Zimmermann, Johannes; Madeddu, Fabio; Courtet, Philippe; Preti, Emanuele
Abstract : Introduction: Prevalence of suicidal thoughts and behaviours is higher among patients with borderline personality disorder than the general population. However, evidence concerning the role of specific borderline symptoms for predicting suicide-related outcomes is lacking and no systematic review/meta-analysis (SR/MA) investigated this topic. Our aim will be to investigate the relationship between any borderline symptom (except criterion 5) and suicide-related outcomes both through an SR/MA and an individual patient data meta-analysis (IPD-MA). Methods: We will search PubMed/MEDLINE, Scopus, Web of Science, Embase, PsycINFO, CINAHL and Cochrane Library databases from 1974 until September 2021. Both published and unpublished studies showing the association between any borderline symptom (except criterion 5) and suicide-related outcomes (death wish, suicidal ideation, suicidal plan, non-suicidal self-injury, deliberate self-harm, suicide attempt, suicidal behaviour disorder, suicide) will be included. Two team members will independently perform the selection of the studies and data extraction, with the supervision of two other members in case of discrepancies; and assess each study with study quality assessment tools by National Institutes of Health and Grading of Recommendations Assessment, Development and Evaluation. Each author will be contacted. If possible, we will perform both random-effect meta-analyses on the collected data (odds, risk, rate ratios or correlations) and an IPD-MA on collected databases. Ethics and dissemination: This study does not require an ethical approval. Results will be publicly disseminated, included in research presentations and published in peer-review journals. PROSPERO registration number: CRD42018078696.